The network building in the organic products market: the case of the Southern Circulation and Trading Circuit of the Rede Ecovida Agroecology (Terr@ Plural, 2023)
This article addresses the market of organic products, highlighting the role of networks for the creation of trading spaces. Based on organic production data and on the analysis of different experiences linked to the Circuito Sul de Circulação e Comercialização de Produtos Agroecológicos da Rede Ecovida de Agroecologia (Southern Circuit of Circulation and Commercialization of Agroecological Products of the Ecovida Agroecology Network), the aim was to discuss and problematize the scales in the networks of organic products, with emphasis on the peasant agriculture. In these terms, the market is formed by disputed territorialities, leading to conflicts between hegemonic and counter-hegemonic agents who use different spatial practices to expand their scales of action and strengthen their respective territorial projects. Peasant agriculture, through multi-scale relationships, has created successful alternatives in the organic products market, strengthening its relative autonomy based on Agroecology.
Keywords: Agroecology; trading; peasantry; market mechanisms